2014
DOI: 10.4993/acrt.22.28
|View full text |Cite
|
Sign up to set email alerts
|

Does standardization of radiofrequency hyperthermia benefit patients with malignancies?

Abstract: Background: Hyperthermia has not been approved as a standard treatment method in oncology. One of the major problems is that there is no reference point for this therapy. Another problem is that radiofrequency hyperthermia has a fatal flaw, the hot spot phenomenon, which does not allow continuation of treatment without lowering the output. Patients and Methods: Hyperthermia treatment was administered either alone or concomitantly with chemotherapy and/ or radiotherapy to 76 consecutive patients with malignanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Thermic treatment was administered using the Thermotron-RF 8 (Yamamoto Vinita Co., Ltd., Osaka, Japan) once per week for 5 weeks with 50 min irradiation. Precise methods of thermal therapy were described elsewhere (16,17,19,20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermic treatment was administered using the Thermotron-RF 8 (Yamamoto Vinita Co., Ltd., Osaka, Japan) once per week for 5 weeks with 50 min irradiation. Precise methods of thermal therapy were described elsewhere (16,17,19,20).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, radiofrequency (RF) hyperthermia using the Thermotron-RF 8 has been administered mainly in Japan but incurs a risk of the 'hotspot' phenomenon, a potentially fatal complication induced by RF treatment itself. To resolve this problem, we established thermal therapy with standardized power escalation principles, i.e., 'neothermia,' and devised a predictive formula for output-limiting symptoms (16,17) which had an adjusted R 2 of 0.99 and variance inflation factor (VIF) values <2. This formula, is as follows: Initial energy output at which an output limiting symptom occurred (Watt)=initial time at which an output limiting symptom occurred (min) x6.162-the thickness of the fat of the abdominal wall (mm)…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study found that the local control was better when less energy was administered than was prescribed [55].…”
Section: How Local Is the Local Treatment?mentioning
confidence: 99%
“…address the former, we established a standardized thermic treatment 16,17) . To address the latter, we developed a predictive formula for output limiting symptoms 18) , which had an adjusted R 2 of 0.99 and variance inflation factor (VIF) values < 2.…”
Section: Gross Tumor Volume Is a Good Predictor Of Rectal Cancer Tumomentioning
confidence: 99%
“…T her m ic t reatment was per for med usi ng t he Thermotron-RF8 (Yamamoto Vinita Co., Ltd., Japan) once a week for 5 weeks each with 50 min irradiation. Precise methods of thermal therapy were described elsewhere 16,17) . A sensor catheter with four temperature points was attached to the skin on the lateral abdomen of 68 patients.…”
Section: Thermal Therapymentioning
confidence: 99%